Project-Based Digital Worksheets with Chemoentrepreneurship to Foster Creative Thinking and Entrepreneurial Interest in Reaction Rates - Nuri Jannati Azzahra; Sri Susilogati Sumarti; Devy Lestari (Universitas Negeri Semarang, 2026)
The teaching of factors affecting reaction rates in high schools still tends to emphasize conceptual aspects and does not fully relate chemical concepts to real-life contexts. This condition prevents students' creative thinking skills and entrepreneurial interests from developing optimally. Therefore, digital teaching materials that can facilitate active, contextual, and meaningful learning are needed. This study aims to develop and test the feasibility and effectiveness of Chemoentrepreneurship-oriented Project-Based Learning Electronic Student Worksheets on the subject of factors affecting reaction rates in improving students' creative thinking skills and entrepreneurial interest. This study used a research and development method with a Four-D model, which includes the stages of definition, design, development, and dissemination. The research subjects were grade XI students at a public high school, who were divided into an experimental class and a control class. Data were collected through expert validation sheets, pre-tests and post-tests, creative thinking ability observation sheets, and entrepreneurial interest questionnaires, then analyzed descriptively and inferentially. The results showed that the developed Electronic Student Worksheets met the criteria of being highly feasible based on expert validation. In addition, it has been proven that the use of these teaching materials can improve students'.